Angiogénese e cancro: da biopatologia à terapêutica. - Bruno Graça; Carla Lunet; Ana Sofía Coelho; Gisela Monteiro; Paulo Freire; Andreia Speidel; Lina Carvalho (Acta Médica Portuguesa, 2004)
Angiogenesis is an important factor in the development of epithelial neoplasias and is useful in the study of progression and metastasis. Neoplastic cells produce angiogenic factors that overtake the antiangiogenic capacity of autoimmune cells. The vascular endothelial growth factor (VEGF) is the most important factor in the neoplastic angiogenesis. In colo-rectal carcinoma the expression of VEGF is parallel with genetic alterations and Duke's grade. In non-small cell lung carcinoma it is possible to define the angiogenic squamous dysplasia that evolves to invasive epidermoid carcinoma. In invasive gastric and lung cancer, the stromal molecules: COX 2, metalloproteinasis and adhesion molecules develop angeogenesis and their validation is important either in and therapy. In breast cancer there is a correlation between the growing of microvessels density, VEGF expression and p53 alterations, pointing to prognosis. Serological values of VEGF may also be used to monitorise the follow up of sarcomas and its reccurrence but vascular metastatic process is not yet completely understood.